2005
DOI: 10.1021/jp052068c
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Spectroscopy, and Spectral Tuning of the Gas-Phase Retinal Chromophore:  The β-Ionone “Handle” and Alkyl Group Effect

Abstract: The low-lying singlet states (i.e. S0, S1, and S2) of the chromophore of rhodopsin, the protonated Schiff base of 11-cis-retinal (PSB11), and of its all-trans photoproduct have been studied in isolated conditions by using ab initio multiconfigurational second-order perturbation theory. The computed spectroscopic features include the vertical excitation, the band origin, and the fluorescence maximum of both isomers. On the basis of the S0-->S1 vertical excitation, the gas-phase absorption maximum of PSB11 is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
115
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(134 citation statements)
references
References 35 publications
16
115
1
2
Order By: Relevance
“…It is thus apparent that the opsins induce a blue-shift of the chromophore max a . Notice that, for the case of Rh, the difference in excitation energy of the relaxed gas-phase chromophore (the N-methylated form of the 6-s-cis,11-cis retinal protonated Schiff base) (29) and of the isolated Rh chromophore (this work) is 0.2 kcal⅐mol Ϫ1 . This demonstrates that the max a change induced by the protein environment is due to effects other than the limited changes in chromophore structure (the main differences are a Ϸ10°in-crease in the C 6 OC 7 single bond torsion and a planarization of the -C 12 AC 11 OC 10 AC 9 OC 8 AC 7 -moiety in the gas-phase structure).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…It is thus apparent that the opsins induce a blue-shift of the chromophore max a . Notice that, for the case of Rh, the difference in excitation energy of the relaxed gas-phase chromophore (the N-methylated form of the 6-s-cis,11-cis retinal protonated Schiff base) (29) and of the isolated Rh chromophore (this work) is 0.2 kcal⅐mol Ϫ1 . This demonstrates that the max a change induced by the protein environment is due to effects other than the limited changes in chromophore structure (the main differences are a Ϸ10°in-crease in the C 6 OC 7 single bond torsion and a planarization of the -C 12 AC 11 OC 10 AC 9 OC 8 AC 7 -moiety in the gas-phase structure).…”
Section: Resultsmentioning
confidence: 82%
“…2B) displays, with respect to the Rh chromophore, a Ͻ0.3 kcal⅐mol Ϫ1 change in excitation energy. In a recent report (29) we have shown that, in the gas-phase, the excitation energy of the retinal chromophore is sensitive to the deformation of the conjugated -framework. Here, the equilibrium structures of iso-Rh and G121L (see Fig.…”
Section: Resultsmentioning
confidence: 92%
“…This system has become a benchmark system for advanced electronic structure methods in recent years (see, for instance, Refs. [103][104][105][106][107][108][109][110][111][112][113][114][115][116][117]. For the channelrhodopsin protein, we employ the M2P2 potential constructed in Ref.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Este tipo de reação é bem conhecido dos organismos vivos, onde encontramos moléculas fotorreceptoras naturais como a rodopsina (responsável pela visão) 24 e a clorofila (fotossíntese) 25 . A visão, por exemplo, inicia quando a luz é focalizada na retina, camada de células que recobre o interior do globo ocular.…”
Section: Fotoquímica Aplicada à Medicina -Terapia Fotoredoxunclassified
“…Essa estratégia tem sido amplamente usada para controlar as geometrias e funções de biomoléculas, nos processos de visão, de materiais orgânicos e de complexos supramoleculares 24,[52][53][54] .…”
Section: Química E Eletrônica Molecular: Movimentos Conformacionais Iunclassified